Integration between Urban Planning and Water Management: Strategies for the Recovery of APPs and Springs in Ijuí/RS - Jachinski, Bruna Carolina; Gai , Carolina Casarin; Plissão , Yuri Lucian; Silveira, Daniel Claudy da; Oliveira, Tarcísio Dorn de (Technical and Scientific Journal Green Cities, 2025)
Objective – To analyze the Recovery Plan for the Urban Streams of Ijuí, focusing on Permanent Preservation Areas (APPs) and the restoration of springs, highlighting the challenges and strategies proposed for environmental recovery and sustainable management of water resources. Methodology – This study is characterized as a case study (Gil, 1991), aimed at analyzing urban environmental management in the municipality of Ijuí/RS, with the Recovery Plan for the Urban Streams as its object. The research adopts a qualitative and quantitative approach of a descriptive and exploratory nature, combining the collection of primary and secondary data with critical interpretation in light of environmental legislation and scientific literature. Originality/relevance – The article contributes by discussing the recovery of urban streams in medium-sized Brazilian cities, a topic still underexplored in the academic literature, especially at the intersection of urban management, environmental legislation, and ecological restoration. Results – The article showed that the diagnosis of the Ijuí Urban Streams Recovery Plan revealed a critical scenario of APPs and urban springs, marked by severe environmental degradation, low self-purification capacity of water bodies, and the presence of geotechnical risks. The analysis also demonstrated that the strategies proposed by the Plan are consistent with best practices in ecological restoration described in the literature, such as riparian vegetation recovery, spring renaturalization, and the creation of ecological corridors. Theoretical/methodological contributions – From an academic standpoint, the article demonstrated the relevance of applying multicriteria diagnostics and spatial analyses in urban watersheds as effective tools to support environmental management. The systematization of the Plan’s findings, compared with legislation and scientific literature, allowed for a methodological discussion on how technical instruments can be interpreted and applied in research on urban sustainability and water management. Social and environmental contributions – The analysis highlights that the recovery of urban APPs and springs can generate positive social and environmental impacts, such as reducing vulnerability to floods, improving water quality, and strengthening water security. At the same time, it emphasizes the potential for community inclusion and the articulation of integrated public policies, indicating pathways for medium-sized Brazilian cities to advance toward more resilient and sustainable urban development models.